Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 60220 species occurrences available in GBIF matching the query: { "and" : [ "Country is Belgium", "TaxonKey is one of (Aponogeton distachyos L.f., Cabomba caroliniana A.Gray, Cherax destructor Clark, 1936, Crassula helmsii (Kirk) Cockayne, Elodea densa (Planch.) Casp., Erythranthe guttata (DC.) G.L.Nesom, Faxonius immunis (Hagen, 1870), Faxonius juvenilis (Hagen, 1870), Faxonius rusticus (Girard, 1852), Faxonius virilis (Hagen, 1870), Heracleum mantegazzianum Sommier & Levier, Heracleum persicum Desf., Heracleum pubescens (Hoffm.) M.Bieb., Houttuynia cordata Thunb., Hydrocotyle ranunculoides L.f., Impatiens glandulifera Royle, Koenigia polystachya (Wall. ex Meisn.) T.M.Schust. & Reveal, Lagarosiphon major (Ridl.) Moss, Ludwigia grandiflora (Michx.) Greuter & Burdet, Ludwigia peploides (Kunth) P.H.Raven, Lysichiton americanus Hultén & H.St.John, Myriophyllum aquaticum (Vell.) Verdc., Myriophyllum heterophyllum Michx., Petasites japonicus (Siebold & Zucc.) Maxim., Pontederia cordata L., Procambarus acutus (Girard, 1852), Procambarus clarkii (Girard, 1852), Procambarus virginalis Lyko, 2017, Saururus cernuus L., Zizania latifolia (Griseb.) Hance ex F.Muell.)", "OccurrenceStatus is Present", "Year is greater than or equal to 2000" ] } The dataset includes 60220 records from 47 constituent datasets: 358 records from iNaturalist Research-grade Observations. 401 records from Update of the giant hogweed (Heracleum mantegazzianum) distribution in Wallonia, Belgium. 4925 records from DEMNA-DNE : Early warning system on Introduced Species in Wallonia. 1400 records from DEMNA-DNE : Exotic plant occurrences in Wallonia. 1397 records from Participatory inventory of the Himalayan balsam within the Dyle basin since 2008. 3 records from VIS - Reference freshwater monitoring in Flanders, Belgium (post 2013). 1200 records from Monitoring of invasive alien plants in the LIFE RIPARIAS areas in Flanders, Belgium. 16 records from Monitoring of invasive alien crayfishes in the Flemish part of the LIFE RIPARIAS areas. 9 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 2754 records from Pl@ntNet automatically identified occurrences. 6 records from Miscellaneous Vascular Plants. 5047 records from VMM - Rat control occurrences in Flanders, Belgium. 206 records from VMM - Inland water macrophyte occurrences in Flanders, Belgium. 229 records from Pl@ntNet observations. 1 records from Royal Belgian Institute of Natural Sciences Crustacea collection. 1 records from Water Framework Directive AGE, Recorder-Lux database. 12 records from INSDC Sequences. 166 records from RATO - daily operations commissioned by the province East Flanders, Belgium. 7290 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 52 records from Meise Botanic Garden Herbarium (BR). 20 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 4 records from Herbarium of Namur. 3498 records from Observations.be - Non-native species occurrences in Wallonia, Belgium. 4 records from Alien macroinvertebrates in Flanders, Belgium. 481 records from Waarnemingen.be - Non-native animal occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from International Barcode of Life project (iBOL). 8 records from SPW ARNE-DNF : Occurrences of introduced species along roadsides in Wallonia. 1 records from Carnet en Ligne. 48 records from N2000-Alien plants along river banks. 3 records from data.mnhn.lu observation data. 368 records from Invasive species - Invasive plants near waterways in West and East Flanders, Belgium. 8 records from Charles University Prague - Herbarium PRC. 1 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 43 records from Collections and observation data National Museum of Natural History Luxembourg. 9 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 28734 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 10 records from VIS - Fishes in inland waters in Flanders, Belgium. 15 records from Living plant collection of Meise Botanic Garden. 611 records from Contrat de Rivière - RIPARIAS: detection and management of aquatic invasive alien species. 593 records from Monitoring of invasive alien species by the Province East Flanders, Belgium. 28 records from Monitoring of fishes and crustaceans by Province East Flanders in Flanders, Belgium. 1 records from RBINS DaRWIN. 75 records from DEMNA-DNE : Exotic animal occurrences in Wallonia, Belgium. 162 records from Invasive species - New Zealand pigmyweed (Crassula helmsii) occurrences in Flanders, Belgium. 5 records from VIS - Non-native fish in Flanders, Belgium. 6 records from Naturalis Biodiversity Center (NL) - Botany. 10 records from Manscape. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences